Spintronics XIV 2021
DOI: 10.1117/12.2596102
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature ferroelectric control of spin-to-charge conversion in GeTe

Abstract: Since its birth in the 1990s, semiconductor spintronics has suffered from poor compatibility with ferromagnets as sources of spin. While the broken inversion symmetry of some semiconductors may alternatively allow for spin-charge interconversion, its control by electric fields is volatile.Ferroelectric Rashba semiconductors stand as appealing materials unifying semiconductivity, large spin-orbit coupling, and non-volatility endowed by ferroelectricity. However, their potential for spintronics has been little e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Varotto et al demonstrated a ferroelectric control of spin-charge conversion at room temperature with GeTe-based structures, with an efficiency comparable to that of Pt 141 .…”
Section: Ferroelectric Control Of the Spin-charge Interconversionmentioning
confidence: 99%
“…Varotto et al demonstrated a ferroelectric control of spin-charge conversion at room temperature with GeTe-based structures, with an efficiency comparable to that of Pt 141 .…”
Section: Ferroelectric Control Of the Spin-charge Interconversionmentioning
confidence: 99%